Metals and molecular carcinogenesis. (17th July 2020) - Zhu, Yusha; Costa, Max
Abstract: Many metals are essential for living organisms, but at higher doses they may be toxic and carcinogenic. Metal exposure occurs mainly in occupational settings and environmental contaminations in drinking water, air pollution and foods, which can result in serious health problems such as cancer. Arsenic (As), beryllium (Be), cadmium (Cd), chromium (Cr) and nickel (Ni) are classified as Group 1 carcinogens by the International Agency for Research on Cancer. This review provides a comprehensive summary of current concepts of the molecular mechanisms of metal-induced carcinogenesis and focusing on a variety of pathways, including genotoxicity, mutagenesis, oxidative stress, epigenetic modifications such as DNA methylation, histone post-translational modification and alteration in microRNA regulation, competition with essential metal ions and cancer-related signaling pathways. This review takes a broader perspective and aims to assist in guiding future research with respect to the prevention and therapy of metal exposure in human diseases including cancer. Abstract : This review focuses on the molecular mechanisms of five Group 1 metal carcinogens in driving cancer and aims to assist in guiding future research with respect to the prevention and therapy of metal exposure.